2003
DOI: 10.1029/2002ja009310
|View full text |Cite
|
Sign up to set email alerts
|

Equatorial electrojet from Ørsted scalar magnetic field observations

Abstract: [1] Previous studies of the longitudinal variation of the local noon electrojet have yielded doubtful results either because of the poor data quality or because the local times of equatorial crossings occurred in the early morning or late afternoon. The recent launch of the Ørsted satellite in a near-circular orbit with slow drift in local time of equatorial crossing has provided the opportunity for researchers to study the electrojet more accurately. Most studies remove the main field using a spherical harmon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 15 publications
5
30
1
Order By: Relevance
“…In particular, it can be seen that the equatorial electrojet forms in the morning hours after sunrise, and, exists from the pre-noon hours until sunset. See Ivers et al (2003) and Lühr et al (2004).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, it can be seen that the equatorial electrojet forms in the morning hours after sunrise, and, exists from the pre-noon hours until sunset. See Ivers et al (2003) and Lühr et al (2004).…”
Section: Resultsmentioning
confidence: 99%
“…One has to examine why the analyses of satellite data by different scientists do not agree with each other and why the conclusions Luhr et al (2004) are not in conformity with the ground magnetic field measurements. Ivers et al (2003) have discussed in detail the reasons for the equatorial electrojet profiles being different from the ground and satellite measurements. They suggested that the combination of long-track and spatial filtering of the satellite data modified the characteristics of the raw electrojet signature.…”
Section: Latitudinal Variations Of X Y and Z For Different Local Hoursmentioning
confidence: 97%
“…Early satellite observations showed diverse results (Cain and Sweeney 1973;Onwumechili and Agu 1981;Langel et al 1993;Kim and King 1999;Jadhav et al 2002;Ivers et al 2003;Lühr et al 2004). More recent studies have established that the longitudinal variation of the daytime equatorial electrojet intensity is often dominated by the so-called "wave-4" pattern with four peaks and four troughs between 0°and 360°longitudes (Le Mouël et al 2006;England et al 2006;Alken and Maus 2007;.…”
Section: Eejmentioning
confidence: 99%